Ptbp2 re-expression rescues axon growth defects in Smn-deficient motoneurons - Salehi, Saeede; Zare, Abdolhossein; Gandhi, Gayatri; Sendtner, Michael; Briese, Michael (Frontiers in Molecular Neuroscience, 2024)
Spinal muscular atrophy (SMA) is a neuromuscular disorder caused by mutations or deletions in the survival motoneuron 1 (SMN1) gene, resulting in deficiency of the SMN protein that is essential for motoneuron function. Smn depletion in mice disturbs axonal RNA transport and translation, thereby contributing to axon growth impairment, muscle denervation, and motoneuron degeneration. However, the mechanisms whereby Smn loss causes axonal defects remain unclear. RNA localization and translation in axons are controlled by RNA-binding proteins (RBP) and we recently observed that the neuronal RBP Ptbp2 modulates axon growth in motoneurons. Here, we identify Smn as an interactor of Ptbp2 in the cytosolic compartments of motoneurons. We show that the expression level of Ptbp2 is reduced in axons but not in the somata of Smn-depleted motoneurons. This is accompanied by reduced synthesis of the RBP hnRNP R in axons. Re-expression of Ptbp2 in axons compensates for the deficiency of Smn and rescues the defects in axon elongation and growth cone maturation observed in Smn-deficient motoneurons. Our data suggest that Ptbp2 and Smn are components of cytosolic mRNP particles, contributing to the precise spatial and temporal control of protein synthesis within axons and axon terminals.